Dear Mrs. LaRue : letters from Obedience School - Teague, Mark. (New York : Scholastic Press, 2002)
Gertrude LaRue receives typewritten and paw-written letters from her dog Ike, entreating her to let him leave the Igor Brotweiler Canine Academy and come back home.
500
500
Accelerated Reader AR
Keywords: Dogs -- Juvenile fiction; Dogs -- Training -- Juvenile fiction; Pets -- Juvenile fiction; Letters -- Juvenile fiction; Humorous stories